The adsorption of phosphate-buffered saline to model films composed of nanofibrillated cellulose and gelatin - Sedat Ondaral; Elif Çelik; Orçun Çağlar Kurtuluş (SAGE Publications, 2019)
Phosphate-buffered saline (PBS) adsorption on model films composed of gelatin and nanofibrillated celluloses (NFCs) with different aldehyde and carboxyl contents was studied by means of the quartz crystal microbalance with dissipation (QCM-D) technique in this study. The results showed that frequency shift (Δ f) due to PBS adsorption increased with increasing gelatin content to 50% in NFC-containing films. The dissipation shift and adsorption rate of PBS followed the same trend. Model films with NFC-1 having 1.22 mmol/g aldehyde and 0.6 mmol/g carboxyl groups adsorbed more PBS than those consisting of NFC-2 with 0.25 mmol/g aldehyde and 1.15 mmol/g carboxyl groups except for film composed of 50% gelatin. However, adsorption rate of PBS was found to be slower for NFC-1 containing film because the acetal and amidol bonds formed by functional groups in the network of cellulose and gelatin needed more time to let PBS migrate into the films.
Keywords: X-Ray Diffraction; Nanofibers; Quartz Crystal Microbalance Techniques; Gelatin; Adsorption; Saline Solution; Cellulose; TP248.13-248.65; Biotechnology; Phosphates; 8. Economic growth